Efficacy of Technical Processes in Heavy Equipment Maintenance - Sotomayor Sancho Dávila, César Rafael (2025)
This study focuses on enhancing the competitiveness of small and medium-sized companies (SMEs) specializing in heavy equipment maintenance. It introduces an innovative model that links the operational efficacy of technical processes to the overall effectiveness of maintenance services. This approach considers all elements of the value chain, including the processes and resources involved at each stage. The research highlights that a gap in the technical development of these processes hinders companies from achieving optimal outcomes due to inconsistency in maintenance methods. To address this challenge, a quantitative study has been conducted to explore the causal relationship between the efficacy of technical processes and the effectiveness of maintenance services. This research study aims to identify strategies that enable companies to improve their performance in this area.